Metode Numbered Head Together (NHT) untuk Meningkatkan Kecerdasan Logika Matematika Anak Usia Dini - Lismayani, Angri; Pratama, Muhammad Isbar (Peneliti.net, 2024)
This research aims to examine how the implementation of the Number Head Together (NHT) method can improve the mathematical logic intelligence of early childhood. This study is a qualitative descriptive research with data collection techniques through interviews, observations, and documentation. The implementation of the Numbered Head Together (NHT) method uses 5 systematic steps that can improve the mathematical logic intelligence of early childhood.